#### Answer

$x=-6$

#### Work Step by Step

$\frac{2x-3}{4}=\frac{x-4}{2}-\frac{x+1}{4}$
$\frac{2x-3}{-4}=\frac{2(x-4)-x-1}{-4}$
$2x-3=2x-8-x-1$
$-3=-x-9$
$x=-9+3$
$x=-6$

Published by
Pearson

ISBN 10:
0-13417-894-7

ISBN 13:
978-0-13417-894-3

$x=-6$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.